2015
DOI: 10.1007/s11269-015-0987-x
|View full text |Cite
|
Sign up to set email alerts
|

Describing the Karst Evolution by the Exploitation of Hydrologic Time-Series Data

Abstract: The importance of the groundwater management of karst aquifers relatively to their complexity requires the knowledge of the subsurface flow and storage behavior. In this study, a methodological approach based on the exploitation of daily spring's discharge data was developed and tested. The methodology makes use of the hydrograph recession curves, the correlograms output, and the logarithmically structured duration curves. This methodological approach was applied to the complex karst system of Louros basin. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Different recession coefficients reflect flow regimes with different hydraulic conductivities [5]. Therefore, the recession coefficient is always used to identify the structural properties (matrix, fractures, and conduit networks) and the karstification degree of a karst aquifer [23,[52][53][54]68,69].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different recession coefficients reflect flow regimes with different hydraulic conductivities [5]. Therefore, the recession coefficient is always used to identify the structural properties (matrix, fractures, and conduit networks) and the karstification degree of a karst aquifer [23,[52][53][54]68,69].…”
Section: Discussionmentioning
confidence: 99%
“…where i represents the media i in the aquifer, Q 0i represents the discharge of media i at t = 0, and n represents the number of sub-regimes or flow components. A karst aquifer can always be divided into different sub-regimes based on the different hydraulic conductivities of the media that comprise it [52][53][54]. Therefore, the modified Maillet equation can be written as:…”
Section: Recession Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kovačič (2010) and Kovačič and Ravbar (2016) claim that the classification of karst aquifers based on time series analysis alone does not adequately describe actual conditions and that other analyses are required to strengthen the results. As such, MRC analysis was also conducted in this study, in accordance with a review by Katsanou et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…(b) The karst system of the Louros Basin consists of carbonate formations of the Ionian zone. From the springs' discharge data for the Eocene limestones of the area, a long memory emerged just as in the previous case (lag time between 70-100 days) corresponding to increased porosity, which is explained by the presence of the epikarst zone [2,37]. It was also found that the very good drainage of the aquifers corresponds to a developed karst system.…”
Section: The Role and Presence Of The Epikarstic Zone In General Andmentioning
confidence: 61%